2018
DOI: 10.3390/ijms19082377
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to Marinobufagenin Reverses Placenta-Induced Fibrosis of Umbilical Arteries in Preeclampsia

Abstract: Background: Previous studies implicated cardiotonic steroids, including Na/K-ATPase inhibitor marinobufagenin (MBG), in the pathogenesis of preeclampsia (PE). Immunoneutralization of heightened MBG by Digibind, a digoxin antibody, reduces blood pressure (BP) in patients with PE, and anti-MBG monoclonal antibody lessens BP in a rat model of PE. Recently, we demonstrated that MBG induces fibrosis in cardiovascular tissues via a mechanism involving inhibition of Fli-1, a nuclear transcription factor and a negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 21 publications
2
31
0
1
Order By: Relevance
“…In the nucleus, phosphorylated PKCδ phosphorylates Fli1, which withdraws Fli1-induced inhibition of the collagen-1 promoter and increases in procollagen expression and collagen production [32] (Figure 1). The mechanism of vascular fibrosis induced by various vascular factors including CS is also implicated in remodeling of spiral uterine arteries, associated with the development of PE [32,37]. Interestingly, the same mechanism of synthesis of collagen-1, Fli1-dependent fibrosis, was found in myocardium of rats with renal failure [38].…”
Section: Fibrosis and Preeclampsiamentioning
confidence: 88%
“…In the nucleus, phosphorylated PKCδ phosphorylates Fli1, which withdraws Fli1-induced inhibition of the collagen-1 promoter and increases in procollagen expression and collagen production [32] (Figure 1). The mechanism of vascular fibrosis induced by various vascular factors including CS is also implicated in remodeling of spiral uterine arteries, associated with the development of PE [32,37]. Interestingly, the same mechanism of synthesis of collagen-1, Fli1-dependent fibrosis, was found in myocardium of rats with renal failure [38].…”
Section: Fibrosis and Preeclampsiamentioning
confidence: 88%
“…In this model, in vivo immunoneutralization of MBG with poly-and monoclonal antibodies produced antihypertensive effect associated with the increase in vascular NKA activity [33,42]. Considering that, (i) MBG stimulates synthesis of collagen, (ii) fibrosis in placenta and umbilical arteries in PE patients is accompanied by elevated placental MBG and a dramatic decrease in Fli-1 level [43], and (iii) PE is associated with vascular stiffening [44,45]; it has been showed that MBG is one of the factors, implicated in pathogenesis of PE via induction of vasoconstriction and vascular fibrosis [41]. In the recent study, it has been shown that the placental levels of Fli-1 were dramatically lower, while collagen-1 levels were higher in both placenta and umbilical arteries in PreE samples compared to the tissues from control noncomplicated pregnancy.…”
Section: Monoclonal Antibodymentioning
confidence: 93%
“…In the recent study, it has been shown that the placental levels of Fli-1 were dramatically lower, while collagen-1 levels were higher in both placenta and umbilical arteries in PreE samples compared to the tissues from control noncomplicated pregnancy. e subsequent treatment of the umbilical artery explants from PE patients with anti-MBG mAb was accompanied by a significant decrease in collagen-1 abundance [43].…”
Section: Monoclonal Antibodymentioning
confidence: 94%
“…После эвтаназии оценивали количество плодов и их среднюю массу, измеряли вес плаценты, оценивали уровень эндоглина в плаценте, sFlt1 в плаценте и кольцах грудной аорты, а также измеряли количество Fli1, коллагена-1, трансформирующего фактора роста бета (ТФР-бета), коллагена-4 в кольцах грудной аорты. Подготовку образцов тканей плаценты, а также колец грудной аорты проводили по ранее отработанной методике [7]. Для оценки содержания МБГ в плазме крови использовали моноклональные анти-МБГ антитела 4G4.…”
Section: материа лы и методы исс ле дованияunclassified